ANALISIS FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KELELAHAN KERJA PADA PEKERJA PEMBUAT KERUPUK OPAK DI DESA NGADIKERSO, KABUPATEN SEMARANG - Birthda Amini Deyulmar; Suroto Suroto; Ida Wahyuni (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2018)
Fatigue means a condition where there is a decreased on someone’s performance because of some factors, such as age, working period, breakfast habits, nutritional status, and work posture. Opak crackers workers in Ngadikerso Village, Semarang District have complaints on physical fatigue, category like pain on the back and shoulder, feeling thirsty frequently, experiencing tremors on limbs. They also have complaints about decreased performance category such as heaviness on head and leg, feeling sleepy, yawning, and standing unstable sometimes. The purpose of this research is to analyze the factors (age, working period, breakfast habit, nutritional status, and work posture) to work fatigue. The type of this research is using cross sectional studywhich is a form of observational study that is analytic descriptive. Population and the specimen of this research are 64 workers. Assessment instrument of work fatigue in this research is SSRT questionnaire. The result of this research is shows that there is connection between work fatigue level and age (p = 0,006), breakfast habit (p = 0,000), nutritional status (p = 0,013) dan work posture (p = 0,001). Besides that there is no relationship between work fatigue level and working period (p = 0,144). In this research, the workers are recommended to serve bread for breakfast substitutes, maintain diet, health checking, and stretching while working.